POLYNEUROPATHY ARISING IN THE COURSE OF GOUT- A CASE REPORT - Özlem YOLERİ and Berrin ÖNGEN and İlker ŞENGÜL and Neşe ÖLMEZ and Asuman MEMİŞ and Figen EŞMELİ (Archives of Rheumatology, 2005)
Polyneuropathy arising in the course of gout may be due to various reasons. Colchicine intake, alcohol abuse and vitamin B12 deficiency are among these. A 65-year-old male patient has been reported to remind the physicians the reasons underlying the polyneuropathy seen in gouty arthritis and emphasize the difficulty of a differential diagnosis.